Scuba divers' behavior and satisfaction in a new marine protected area: Lessons from the implementation of a best practices program - Giglio, Vinicius J.; Marconi, Marina; Pereira-Filho, Guilherme H.; Leite, Kelen L.; Figueroa, Apoena C.; Motta, Fabio S. (Ocean & coastal management, 2022)
Subtropical reefs have suffered from increasing threats and impacts mainly from anthropogenic activities. These reefs also have socioeconomic relevance being in many locations an important income source through recreational activities. This study aimed to assess the potentially damaging behaviors of scuba divers on benthic reefs organisms in the first year of a new Brazilian diving destination, the Alcatrazes Archipelago Wildlife Refuge. We also assessed diver satisfaction to verify the effects of management measures on diver experience. Management measures were implemented through a best practices program aiming to improve low-impact diver behavior. Scuba divers caused the lowest contact rate with the reef described in the literature, maintaining low rates of potentially damaging behaviors over the year. Overall, each diver made an average of 0.63 contacts with the reef and 0.06 with the reef biota per 45 min of dive. Most of the contacts were unintentional and occurred in the first 10 min of the dive. The overall satisfaction of divers was high in all seasons. However, regarding specific attributes, experienced divers were more sensitive to increased underwater supervision. Our results highlight the effectiveness of continued initiatives like best practices program to improve low-impact diver behavior. Visitation monitoring programs are essential to understand the behavior of scuba divers and how the restrictions may affect diver enjoyment in reef environments.